Language acquisition : the age factor - Singleton, D. M. (David Michael) (Second language acquisition, 2004)
The authors examine the evidence relative to the idea that there is an age factor in first and second language acquisition and goes on to explore the various explanations that have been advanced to account for such evidence. Finally, it looks at educational ramifications of the age question.